IODIMETRIC DETERMINATION OF SULFUR-CONTAINING ORGANIC REDUCTANTS IN ACIDIC AND NEUTRAL MEDIA: UDC 543.432'831 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
The paper discusses the principles of iodimetry and iodometry for the titrimetric (visual and electrochemical establishment of the titration end point), photometric and solid phase spectrophotometrical determination of sulfuring organic reductants in acidic and neutral media. These methods overcome the shortcomings of iodimetry and iodometry caused by the sublimation of iodine and the ability of iodide ions to be oxidized in acidic media by atmospheric oxygen. The class of sulfur containing organic compounds with respect to their properties as reducing agents has been discussed. A critical review of the methods for iodimetric determination of mercaptopyridines, mercaptopyrimidines, thiols and other sulfur-containing organic compounds in acidic and neutral media has been done. The mechanisms of their oxidation by iodine has been considered. In the case of quantitative running of the reaction (2RSH + I2 → RS-SR + 2HI) the iodometric quantitative determination of thiols takes place. Metrological characteristics of iodometric determination of captopril С9Н15NO3S in pharmaceutical preparations have been discussed in detail. In the cases when the formation of disulfide by oxidation of thiols is not stoichimetric, or when the reaction rate is too low or when the reaction is reversible, which normally leads to the equilibrium between the analyte and the titrant (iodine), it is impossible to successfully perform the determination of organic sulfur-containing reducing agents. In such cases iodimetric titrimetry in an alkaline medium (in fact, it appears to be the titration by strong oxidants, such as the iodate(I) and iodate(V) can be used).
Keywords: organic sulfur containing reducing agents; tuiols; captopril; iodimetry; acidic media; neutral media